THE IDENTITY OF SOME BURMAN SPECIES - kostermans, a. j. g. h. (Research Center for Biology, 1969)
Burman (Thesaurus zeylanicus, 1737) depicted on tab. 79 Nux Moschata, spuria, sylvestris, Caryophylli arboris, oppositis, Nobis.The plate depicts a sterile branch with conspicuous, stalked, perulateleaf buds. The local name is given as Iryaghedhi (cited from Mus. Zeyl.,p. 58). Linnaeus edumerated the species in Fl. Zeyl., p. 590 under